إطار مقترح لتطوير نظام اختيار وتدريب القيادات الإدارية التربوية - محمد راضي, مرفت (جامعة الوادي - University of Eloued, 2015)
ملخص الدراسة هدفت الدراسة الوقوف على واقع نظام اختيار وتدريب القيادات التربوية بمؤسسات التربية والتعليم في قطاع غزة في ضوء مدخل الإدارة الإستراتيجية، حيث استخدمت الباحثة المنهج الوصفي التحليلي، وكان من أبرز نتائجها أن نظام اختيار وتدريب القيادات التربوية في مؤسسات التربية والتعليم يفتقر إلى استخدام الطرق الحديثة ، وضعف اهتمام القيادات التربوية بالتطوير، والاقتصار على تسيير العمل والمشكلات الحالية، وانخفاض كفاءة البرامج التدريبية المقدمة من وزارة التربية والتعليم ؛ مما أثر سلبا على نقل التدريب إلى الواقع العملي، وأن فلسفة نظام التدريب في وزارة التربية والتعليم غير واضحة، وهناك قصور في التحديد الفعلي للاحتياجات التدريبية للقيادات التربوية. واقترحت الدراسة إطاراً مستقبلياً لتطوير نظام اختيار وتدريب القيادات الإدارية التربوية في المؤسسات التعليمية في ضوء مدخل الإدارة الإستراتيجية، ومتطلبات تنفيذ الإطار المقترح بنجاح، مع تحديد المعوقات المتوقعة أمام تنفيذ الإطار المقترح وسبل التغلب عليها . Abstract: This study aimed to identify the reality of system selection and training of educational leaders education institutions and education in the Gaza Strip in light of the entrance to the strategic management, where the researcher used the descriptive analytical method, and was the highlight of the results that the system of selection and training of educational leaders in the educational institutions lacked the use of modern methods, poor interesting educational leaders development, and limited to conduct the work and the current problems, and low efficiency training programs provided by the Ministry of Education; negatively affecting the transfer of training to practice, and that philosophy training system in the Ministry of Education is not clear, and there is a lack in the selection actual training needs educational Leadership. A future study suggested a framework for the development of the system of selecting and training educational administrative leaders in the educational institutions in the light of the entrance to the strategic management, and the requirements of the successful implementation of the proposed framework, with the expected identify constraints to the implementation of the proposed framework and ways to overcome them.
مقال
Keywords: القيادات التربوية.التعليم.التطوير.التدريب.الادارة